A non-equilibrium control oriented model for the pressurizer dynamics. (July 2018) - Pini, Alessandro; Cammi, Antonio; Colombo, Luigi; Tigliole, Andrea Borio
Abstract: This paper deals with a new Control Oriented Model (COM) aimed at studying the dynamic behaviour of the pressurizer in Pressurized Water Reactors (PWRs). In literature, most of the pressurizer COMs treat the vapour and the water filling the system as a homogeneous mixture by adopting the thermodynamic equilibrium assumption. This hypothesis involves a reduced set of governing equations that is suitable for the study of the pressurizer dynamics in a simplified way since interphase and non-equilibrium phenomena (e.g., water drops and vapour bubbles generation) are neglected. To overcome this limitation, an innovative COM based on the non-equilibrium approach is developed. The new model is obtained from closed-rigid system mass, energy and volume balances and allows selecting a different thermodynamic state for each phase, according to the non-equilibrium framework. In addition, while equilibrium models take into account only the heat transfer from the electrical heating of PWR pressurizers, the new COM considers also the following processes occurring in the system volume: the water drops and vapour bubbles generation (inside the vapour and liquid phase, respectively), the condensation on sprayed drops, the heat exchange between vapour and water and thermal losses toward the external environment. The new COM is also characterized by a multiple control volume formulation to reach a good accuracy for several transients (also the complete emptying) that can be experimented by a pressurizer. The experimental data of "loss-of-load" transients in the Shippingport reactor are used to assess the new COM. A code to code comparison is carried out using RELAP5 as reference. Highlights: A control oriented model for the dynamics of the pressurizer is validated against experimental data. For complete emptying transients, the model results are compared with those achieved with RELAP5. A non-equilibrium thermodynamic framework is adopted to treat the different phases. A multiple control volume formulation is used to enhance the accuracy of the model. Evaluate the axial temperature distribution in the liquid phase is important to achieve good results.